The effect of exchange rate movements on heterogeneous plants: A quantile regression analysis - Ben Tomlin; Loretta Fung (Bank of Canada, 2010)
In this paper, we examine how the effect of movements in the real exchange rate on manufacturing plants depends on the plant's placement within the productivity distribution. Appreciations of the local currency expose domestic plants to more competition from abroad as export opportunities shrink and import competition intensifies. As a result, smaller less productive plants are forced from the market, which truncates the lower end of the productivity distribution. For surviving plants, appreciations can lead to a reduction in plant size, which, in the presence of scale economies, can lower productivity. We examine these mechanisms using quantile regression, which allows for the study of the conditional distribution of industry productivity. Using plant-level data that covers the entire Canadian manufacturing sector from 1984 to 1997, we find that many industries exhibit a downward sloping quantile regression curve, meaning that movements in the exchange rate do, indeed, have distributional effects on productivity.
Keywords: D21; F1; L16; L60; 330; Productivity; Exchange rates; Market structure and pricing; Wechselkurspolitik; Wettbewerb; Unternehmensentwicklung; Produktivität; Betriebliche Preispolitik; Verarbeitendes Gewerbe; Kanada